2015
DOI: 10.1002/syn.21811
|View full text |Cite
|
Sign up to set email alerts
|

The sigma agonist 1,3-Di-o-tolyl-guanidine reduces the morphological and behavioral changes induced by neonatal ventral hippocampus lesion in rats

Abstract: Sigma (σ) receptors have generated a great deal of interest due to their possible role in psychosis, neuroprotection, and various other behaviors including addictive processes. Sigma receptors have been located in brain areas involved in motor functions, including the dopaminergic projections from the substantia nigra to the striatum. Evidence suggests that one of their major roles might be to regulate the activity of the glutamatergic system via the N-methyl-D-aspartate receptor. The sigma receptor agonist 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…This chemical is a substance commonly used in polymerization and vulcanization processes in industry, thus likely to occur in water. Since, this compound has also been characterized as having antidepressant properties, 44 it may well have some ecotoxicological relevance and deserves future studies. Some of the remaining chemicals detected are sulfonates.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…This chemical is a substance commonly used in polymerization and vulcanization processes in industry, thus likely to occur in water. Since, this compound has also been characterized as having antidepressant properties, 44 it may well have some ecotoxicological relevance and deserves future studies. Some of the remaining chemicals detected are sulfonates.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…In view of its acute toxicity to aquatic organisms [13], DPG is classified as a PMT substance and has received considerable attention as an emerging PMOC, as exemplified by its detection in surface water [11,[14][15][16][17][18][19][20][21][22][23]. Similar to DPG, 1,3-di-o-tolylguanidine (DTG) is a guanidine derivative that has been detected in water [2,24,25] and examined in terms of its toxicity [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Sigma receptors (σR) are unique drug-binding proteins found in the central nervous system [118], which are located in brain regions involved in motor function, including dopaminergic projections from the substantia nigra to the striatum [119]. The σR 1 agonist DTG reverses behavioral and neuromorphological changes induced by ventral hippocampal lesions in neonatal rats [120]. It was found that circRNA HIPK2 (circ HIPK2) acts as a sponge of miR124-2HG targeting to regulate σR 1 expression and astrocyte activation, which has been shown to attenuate neuroinflammation through the cooperation of cellular autophagy and ER stress [121].…”
Section: Lncrnas and Circrnasmentioning
confidence: 99%